If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 2) + -1(2x + -8) = 0 Reorder the terms: 4(2 + x) + -1(2x + -8) = 0 (2 * 4 + x * 4) + -1(2x + -8) = 0 (8 + 4x) + -1(2x + -8) = 0 Reorder the terms: 8 + 4x + -1(-8 + 2x) = 0 8 + 4x + (-8 * -1 + 2x * -1) = 0 8 + 4x + (8 + -2x) = 0 Reorder the terms: 8 + 8 + 4x + -2x = 0 Combine like terms: 8 + 8 = 16 16 + 4x + -2x = 0 Combine like terms: 4x + -2x = 2x 16 + 2x = 0 Solving 16 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 2x = 0 + -16 Combine like terms: 16 + -16 = 0 0 + 2x = 0 + -16 2x = 0 + -16 Combine like terms: 0 + -16 = -16 2x = -16 Divide each side by '2'. x = -8 Simplifying x = -8
| 9k+5=7-3k | | -3x^2+48=0 | | -44-9x=-31-3x | | 60x=50(x+36) | | 2x(3+5)=25 | | 2x(3+5)= | | 3y-3+9=8y+6-5y | | Z^2+11z+24= | | 72x^3+32x^4-16x^5=0 | | 12b^3-9b^2=0 | | a^2-3a-40=0 | | X^3-3y^3z^2= | | a^2+2a-17=-2 | | 8x^2+22x+121=0 | | 5x=2(3+x) | | 7x=3x^2-6 | | (x)*(x^2+3)=35 | | (b+3)(b-6)=0 | | x^3+3x-35=0 | | 5x^2+11x=-2 | | 3m-35=21+14m | | 7x+12y=200 | | 4x^2=21x-5 | | 3m-35=12+4m | | 7(x-7)=126 | | -6(10-4x)=-3(-12-8x) | | -6y-14=7y+25 | | 2(2y-1)-2(2y)=2 | | x(5x-8)=13 | | 3x-9x^3= | | B=9-a | | 3x(x+1)=(2x+3)(x+1) |